Pengaruh Umur Petani, Luas Lahan Garapan, Serangan Hama atau Penyakit serta Produktivitas Kakao terhadap Keputusan Petani Mengganti Tanaman Kakao Menjadi Nilam di Desa Puduria Jaya Kabupaten Konawe Selatan - La Ode Alwi; Bahari Abdullah; Budiyanto Budiyanto; Abdul Gafaruddin; Juniardin Juniardin (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Cocoa and patchouli plants are the two primary commodities in Indonesia's agricultural sector. Technically and economically, cocoa and patchouli cultivation have advantages and disadvantages. These advantages and disadvantages will, of course, impact the costs and revenues of farming. Meanwhile, farmers cultivating cocoa or patchouli commodities aim to obtain maximum income. However, some farmers in South Konawe Regency have decided to switch from cocoa to patchouli. Thus, this study aims to analyze the influence of farmer age, area of ​​cultivated land, pest and plant disease attacks, and cocoa productivity on farmers' decision-making to replace cocoa plants with patchouli. Puduria Jaya Village, part of South Konawe Regency, was chosen as the study location. The study was conducted in April 2020. This study determined 60 farmers who cultivate cocoa and patchouli as the study population. The census method was used to determine the sample of farmers. The variables observed were the farmer's decision to change crop types, age, cultivated land area, pest and plant disease attacks, and cocoa plant productivity. Interviews were carried out for data collection. The collected data was analyzed using binary logistic regression. The results of data analysis show that the productivity of cocoa plants significantly influences the decision-making opportunity for farmers to replace cocoa plants with patchouli. Meanwhile, the farmer's age, cultivated land area, pest attacks, and plant diseases do not have a significant effect. The greater the decline in the productivity of cocoa plants, the more excellent the opportunity for farmers to make decisions to replace cocoa plants with patchouli. Therefore, easy and cheap cocoa cultivation technology is needed to increase the productivity of cocoa farming.